Effects of exposure to 12C and 4He particles on cognitive performance of intact and ovariectomized female rats. (August 2019) - Rabin, Bernard M.; Miller, Marshall G.; Larsen, Alison; Spadafora, Christina; Zolnerowich, Nicholas N.; Dell'Acqua, Lorraine A.; Shukitt-Hale, Barbara
Abstract: Exposure to the types of radiation encountered outside the magnetic field of the earth can disrupt cognitive performance. Exploratory class missions to other planets will include both male and female astronauts. Because estrogen can function as a neuroprotectant, it is possible that female astronauts may be less affected by exposure to space radiation than male astronauts. To evaluate the effectiveness of estrogen to protect against the disruption of cognitive performance by exposure to space radiation intact and ovariectomized female rats with estradiol or vehicle implants were tested on novel object performance and operant responding on an ascending fixed-ratio reinforcement schedule following exposure to 12 C (290 MeV/n) or 4 He (300 MeV/n) particles. The results indicated that exposure to carbon or helium particles did not disrupt cognitive performance in the intact rats. Estradiol implants in the ovariectomized subjects exacerbated the disruptive effects of space radiation on operant performance. Although estrogen does not appear to function as a neuroprotectant following exposure to space radiation, the present data suggest that intact females may be less responsive to the deleterious effects of exposure to space radiation on cognitive performance, possibly due to the effects of estrogen on cognitive performance.